Utilization Of Geographic Information System (Gis) For Selection Of Idle Pond For Vannamei Shrimp Cultivation - Aris, Muhammad; Wahiddin, Nurhalis; Irham, Irham (Sam Ratulangi University, 2022)
Land suitability is one aspect that determines the success of vannamei shrimp cultivation in coastal pond areas. Cultivation of vannamei shrimp in ponds has a spatial component as well as differences in the biophysical and socio-economic characteristics of each location. Many ponds that are intensively managed have not taken advantage of the advantages of Geographical Information Systems (GIS) in selecting locations and managing vannamei shrimp culture, which is important to do to avoid business failure. This study used a survey method to collect data on water quality parameters (acidity / pH, temperature, salinity, dissolved oxygen / DO, nitrate, and phosphate). Analysis of land suitability for vannamei shrimp cultivation in ponds using the scoring method, each water quality parameter is weighted and a score is then divided into 4 land suitability classes, namely classes S1 (Very Suitable), S2 (Sufficiently Suitable), S3 (Conditional Appropriate), and N (Unsuitable). The results showed that the vannamei shrimp pond land suitability map produced a thematic map of the suitability of the vannamei shrimp pond land which had a total area of 13.65 ha of vannamei shrimp and had 4 levels of suitability, namely very suitable class (S1) with an area of 3.96 ha, a class that appropriate (S2) has an area of 7.8 ha, a moderately suitable class (S3) has an area of 0.85 ha, and an unsuitable class (N) has an area of 1.04 ha.Keywords: Litopenaeus vannamei; Water quality; Land Suitability; Geographical Information SystemsAbstrakKesesuaian lahan merupakan salah satu aspek yang menentukan keberhasilan kegiatan budidaya udang vannamei di wilayah tambak pesisir. Budidaya udang vannamei di tambak memiliki komponen keruangan serta perbedaan karakteristik biofisik dan social ekonomi dari setiap lokasi. Banyak tambak yang dikelola secara intensif belum memanfaatkan kelebihan Sistem Informasi Geografis (SIG) dalam melakukan pemilihan lokasi dan pengelolaan budidaya udang vannamei, dimana hal tersebut penting dilakukan untuk menghindari kegagalan usaha. Penelitian ini menggunakan metode survei untuk pengambilan data parameter kualitas air (keasaman/pH, suhu, salinitas, oksigen terlarut/DO, nitrat, dan fosfat). Analisis kesesuaian lahan budidaya udang vannamei di tambak menggunakan metode skoring, parameter kualitas air masing-masing diberi bobot dan skor yang kemudian dibedakan menjadi 4 kelas kesesuaian lahan yaitu kelas S1 (Sangat Sesuai), S2 (Cukup Sesuai), S3 (Sesuai Bersyarat), dan N (Tidak Sesuai). Hasil penelitian didapatkan peta kesesuaian lahan tambak udang vannamei menghasilkan peta tematik kesesuaian lahan tambak udang vannamei memiliki total luas tambak udang vannamei seluas 13,65 Ha serta memiliki 4 tingkat kesesuaian yaitu kelas sangat sesuai (S1) dengan luasan sebesar 3,96 Ha, kelas yang sesuai (S2) memiliki luasan sebesar 7,8 Ha, kelas yang cukup sesuai (S3) memiliki luasan sebesar 0,85 Ha, dan kelas yang tidak sesuai (N) memiliki luasan sebesar 1,04 Ha.Kata Kunci: Litopenaeus vannamei, Kualitas Perairan; Analisa Kesesuaian; Sistem Informasi Geografis